The National Plan of Borders in Brazil: A New Militarization Process? - Santos, Gislene (2017)
By the end of 20th century, border-related discourses of the space emerged in the international scene. On the one hand, globalization apologists proclaimed a new era characterized by the end of the national states and the porosity of international borders. On the other hand, during the 1980s, surveillance techniques started to be used all along the borders. In Brazil, the geopolitics of borders is also present. Actually, its borders are shared with ten countries and were considered as an area of national strategy, economic interest and public security during the 1990s. In this article, we analyze the “Plano Nacional de Fronteira” (PNF) [National Plan of Borders] implemented by the Bazilian government in 2011 with the installation of a set of technical and surveillance systems all along the border between Brazil and Paraguay. To approach the plan, we will examine the set of devices (rules, discourses, procedures, laws, resources, information systems, and technical objects) installed in this border area.